Rapid axonal transport in focally demyelinated sciatic nerve - Armstrong, R (J Neurosci, 1987)
Focal demyelination was produced in rat sciatic nerve by unilateral intraneural injection of anti-galactocerebroside serum. A functional lesion was confirmed by the presence of nerve conduction block. Histologically, this corresponded to demyelination of 50–70% of the fibers in nerve cross sections; axonal structures appeared intact. At the time of maximal demyelination (7 d), 35S-methionine or 3H-fucose was injected bilaterally into the spinal cord ventral horn. At later times (5 hr-7 d), the sciatic nerve was removed and radioactivity in successive nerve segments was quantitated. The transport rates (approximately 260 mm/d) and the composition of transported proteins and glycoproteins (separated on 7–15% polyacrylamide gradient gels) were not altered in lesioned nerves relative to contralateral control nerves. Light microscopic autoradiographic analysis revealed a similar localization of axonally transported and deposited glycoproteins in demyelinated and control fibers. Initially (8 hr), the majority of label was over axons. Labeled glycoproteins remaining in the nerve after 1 week were retained mainly in axolemmal regions. We conclude that acute focal primary demyelination does not lead to major alterations in the transport or deposition of newly synthesized macromolecules.